2017
DOI: 10.21003/ea.v163-18
|View full text |Cite
|
Sign up to set email alerts
|

Product quality as a condition for maximisation of profit: accounting and control aspects

Abstract: The article considers approaches to the interpretation of the essence of the concept of quality according to both scientific and international quality standards ISO 9000. The authors have presented an analytical assessment of the commodity structure of import and export of agricultural and food products in Ukraine and its impact on the improvement of product quality. It has been emphasised on the need to attract investments and to strengthen the capacity of the State related to the manufacture products with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Manufacturers in Poland also gained the highest turnover per employee in the period after the year 2012 among Visegrad 4 member countries that indicates a growing financial efficiency of labour force usage in Poland in comparison with decreasing or stagnating labour force efficiency in other Visegrad 4 member countries after the year 2012. This observed development in Poland concerning to increasing efficiency of the workforce among food manufacturers is consistent with the finding of Marchuk & Fabiianska (2017) or Zielinska-Chmielewska & Smutka (2018), who point out at factors of effectiveness and efficiency for maintaining competitiveness and profitability of food processing companies both in EU member and candidate countries. Findings of the labour force efficiency are furtherly discussed via the development of total labour force and cost of employees among Visegrad 4 member countries (see Fig.…”
Section: Empirical Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Manufacturers in Poland also gained the highest turnover per employee in the period after the year 2012 among Visegrad 4 member countries that indicates a growing financial efficiency of labour force usage in Poland in comparison with decreasing or stagnating labour force efficiency in other Visegrad 4 member countries after the year 2012. This observed development in Poland concerning to increasing efficiency of the workforce among food manufacturers is consistent with the finding of Marchuk & Fabiianska (2017) or Zielinska-Chmielewska & Smutka (2018), who point out at factors of effectiveness and efficiency for maintaining competitiveness and profitability of food processing companies both in EU member and candidate countries. Findings of the labour force efficiency are furtherly discussed via the development of total labour force and cost of employees among Visegrad 4 member countries (see Fig.…”
Section: Empirical Results and Discussionsupporting
confidence: 89%
“…So, it could be partially concluded that manufacturers settled in Poland gained in both observed periods of years 2009 and 2017 significantly higher mean values of total assets turnover in comparison with other Visegrad 4 member countries at significance level 10 %. According to findings of e. g. Marchuk & Fabiianska (2017) investments to new production technologies are regarded to be a crucial factor in meeting food safety and quality standards. On the contrary, investments are decreasing total assets turnover in the short-run perspective.…”
Section: Figure 5 Decomposition Of Influencing Factors Of Indicator mentioning
confidence: 99%
“…This situation indicates that the government's financial reports still do not fully meet the criteria of reliability (reliable). According to Okaro (2017) many factors can affect the quality of financial reports, such as government accounting standards, government accounting systems, human resource competence (Marchuk, 2017). According to Aini (2018) the competence of human resources is an important factor in compiling a company's financial statements.…”
Section: Introduction *mentioning
confidence: 99%
“…However, they had to adapt the composition and pro perties of their products to the requirements of new markets, especially from an economic point of view, as living standards were low there and it would not be possible to sell foreign products made with the use original recipes. Developed countries accepted high quality products as one of the main sources of their national wealth (Marchuk & Fabiianska, 2017). However, the situation has changed: living standards are slowly levelling off and the countries of Central and East Europe (CEE) are no longer satisfied with the lower quality of goods, which in Western countries have a different composition, but are often sold in the same or very similar packaging.…”
Section: Introductionmentioning
confidence: 99%